Worldview and mind religious thought and psychological development - Webb, Eugene, 1938- (Eric Voegelin Institute series in political philosophy., 2009)
"Looking at a broad spectrum of religions, Webb examines the relation between religion and modernity and explores what psychological analysis reveals about the relationship between stages of psychological development and ways of being religious that range from closed-minded to open-minded tolerance"--Provided by publisher.